1998
DOI: 10.1021/la970951z
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Two-Dimensional Nanometer Size Clusters of Partially Fluorinated Long-Chain Acids

Abstract: Two-dimensional molecular clusters of a few tens nanometer size were found in spread monolayers of a series of partially fluorinated long-chain acids. Atomic force microscopy images have revealed that the size of the clusters is sharply monodisperse. The size changes systematically with changing structure of the hydrophobic chain of the amphiphiles. The smallest cluster has a circular shape of 17 nm diameter. One cluster is composed of about 700 film molecules. These clusters gather to form macroscopic domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 37 publications
4
92
0
Order By: Relevance
“…[12][13][14] However, an antiparallel conformation for FnHm diblocks [15] and the formation of as mecticb ilayer [16] have been proposed, too. Disk-like and striped surface domains were also reportedf or partially fluorinated carboxylic acids [17] and partially fluorinated diether glycerols, [18] respectively.S urfaced omains of variouss hapes were also published for combinations of fluorinated amphiphiles (phosphates, diethyl glycerols) with hydrocarbon and fluorocarbon oils [19] or phospholipids. [20][21] Since FnHm domains can be transferred onto solid substrates even at av ery low surface pressure p % 0mn m À1 , [22] it was suggested that the self-assembly of the FnHm is dependent on surface concentration but not on surface pressure.…”
Section: Introductionmentioning
confidence: 86%
“…[12][13][14] However, an antiparallel conformation for FnHm diblocks [15] and the formation of as mecticb ilayer [16] have been proposed, too. Disk-like and striped surface domains were also reportedf or partially fluorinated carboxylic acids [17] and partially fluorinated diether glycerols, [18] respectively.S urfaced omains of variouss hapes were also published for combinations of fluorinated amphiphiles (phosphates, diethyl glycerols) with hydrocarbon and fluorocarbon oils [19] or phospholipids. [20][21] Since FnHm domains can be transferred onto solid substrates even at av ery low surface pressure p % 0mn m À1 , [22] it was suggested that the self-assembly of the FnHm is dependent on surface concentration but not on surface pressure.…”
Section: Introductionmentioning
confidence: 86%
“…C 8 F 17 COOH (Zhu et al, 1999) or C 10 F 21 COOH (Kato et al, 1998), or phosphocholine and dimorpholinophosphate derivatives) can spontaneously form tightly packed, thin, insoluble films (Langmuir films) on surfaces and at interfaces. Mixtures of C 8 F 17 COOH with the hydrocarbon sulfonate C 18 F 37 SO 3 Na form well separated monolayers when transferred on mica.…”
Section: Aptitude For Self-assembly-interfacial Film Formationmentioning
confidence: 99%
“…Thus, lateral compression decreases the intermolecular distance, causing the micelles to disappear. However, in some cases, the micelles continue to appear even at high surface pressures 5 . LB films of partially fluorinated compounds often exhibit topologies that consist of surface micelles; these compounds include partially fluorinated alkanoic acids 3,5 and alkanes 4 .…”
Section: Afm Observationsmentioning
confidence: 99%
“…LB films of partially fluorinated compounds often exhibit topologies that consist of surface micelles; these compounds include partially fluorinated alkanoic acids 3,5 and alkanes 4 . Kato and coworkers have reported that the formation of surface micelles is induced by the rapid evaporation of the solvent when it is being spread on the substrate surface 5 .…”
Section: Afm Observationsmentioning
confidence: 99%